TMOD-41. TWO NOVEL SETS OF PATIENT DERIVED ORTHOTOPIC XENOGRAFT MOUSE MODELS (PDOX) ESTABLISHED FROM MATCHING PRIMARY AND RECURRENT PEDIATRIC BRAIN TUMORS. Issue 11 (6th November 2017) - Du, Yuchen; Braun, Frank; Zhang, Huiyuan; Qi, Lin; Lindsay, Holly; Kogiso, Mari; Zhao, Sibo; Kool, Marcel; Stephan, Clifford; Li, Xiao-Nan
Abstract: BACKGROUD AND PURPOSE: It is imperative to gain a better understanding of biological changes that occur during tumor progression/evolution/recurrence to facilitated the development of new anti-recurrent therapies. METHODS: Single patient tumor cells were immediately dissociated, cultured in vitro or/and transplanted into mouse brains corresponding to the patient's tumor location. Whole genome DNA methylation, transcriptomic profiling and RNA sequencing were performed in addition to immunohistological phenotypes. Standard therapies which follow clinical regimen were conducted as well in tumor xenografts. RESULTS: We successfully established two sets of matched primary and recurrent PDOX models. Compared with the primary tumors, the tumor-take rate of the recurrent tumors (obtained 9 months after chemo-therapy and stem cell rescue) with shortened tumor onset time increased from 70% of primary tumor 19850PNET to 100% of recurrent 22909PNET (piece#1) and 23542PNET (piece#2) with significantly shorten animal survival times (4-5 months to 2-3 months). In the second set of PDOX models derived a low grade ganglioglioma (100815GGG) and a matching recurrent glioblastoma (104488GBM), progressive phenotypes with decreased tumor onset time (from 5 months to 3 months) was also noted. RNA sequencing reveals preserved and newly mutated genes in recurrent tumors. High-throughput drug screening using cultured patient tumor cells 100815GGG and 104488GBM discovered a shared and a diverse panel of therapeutic targets that could be selected further for in vivo drug treatment in future. Standard chemo-therapy were conducted in xenografts for primary 19850PNET and recurrent 23542PNET tumor. Chemo-drug administration significantly extend survival time of recurrent tumor in contrast to primary tumor. Molecular phenotypes such as genomic methylation and transcriptome profile are underway. CONCLUSION: Two sets of matched primary and recurrent pediatric brain tumors, PNET/PNET and GGG/GBM, were successfully established in pediatric orthotopic mice tumor models (PDOXs) providing clinically-relevant and biologically-accurate animal model systems for development of novel therapeutic targets.